2019
DOI: 10.12657/folmal.027.015
|View full text |Cite
|
Sign up to set email alerts
|

Land snail fauna of the Mekong Delta Limestone Hills (Cambodia, Vietnam): Notharinia Vermeulen, Phung et Truong, 2007, and a note on Plectostoma A. Adams, 1865 (Mollusca: Gastropoda: Caenogastropoda: Diplommatinidae)

Abstract: Diplommatinidae; formerly included in Pupinidae) are described from limestone hills on the east flank of the Mekong Delta, in Vietnam and Cambodia. A map showing the distribution of all ten species now known from the area is presented. In addition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…General shell characters were further divided into detailed sub-characters exclusively for the descriptions of the representatives of the “scaly group” of Bornean Georissa . The assessed morphological characters follow the descriptions made by Godwin-Austen (1889), Gredler (1902), Haase and Schilthuizen (2007), Smith (1893, 1895), Thompson and Dance (1983), van Benthem-Jutting (1966), Vermeulen and Junau (2007), and Vermeulen et al (2015). Note that color indications always refer to living or freshly dead specimens, as the color in older specimens usually degrades, with an exception for Georissa scalinella (van Benthem-Jutting, 1966), where only old collection specimens were available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General shell characters were further divided into detailed sub-characters exclusively for the descriptions of the representatives of the “scaly group” of Bornean Georissa . The assessed morphological characters follow the descriptions made by Godwin-Austen (1889), Gredler (1902), Haase and Schilthuizen (2007), Smith (1893, 1895), Thompson and Dance (1983), van Benthem-Jutting (1966), Vermeulen and Junau (2007), and Vermeulen et al (2015). Note that color indications always refer to living or freshly dead specimens, as the color in older specimens usually degrades, with an exception for Georissa scalinella (van Benthem-Jutting, 1966), where only old collection specimens were available.…”
Section: Methodsmentioning
confidence: 99%
“…Previous taxonomic treatments of Bornean Georissa (Godwin-Austen 1889, Gredler 1902, Haase and Schilthuizen 2007, Smith 1893, 1895, Thompson and Dance 1983, van Benthem-Jutting 1966, Vermeulen and Junau 2007, Vermeulen et al 2015) revealed that shell shape and size, as well as sculptural patterns on the whorls are important characters for species delimitation. Given the small size of these shells, great benefits can be had from the use of scanning electron microscopy and X-ray microtomography, which are able to show detailed microscopic sculpture patterns and the inner part of the shell.…”
Section: Introductionmentioning
confidence: 99%
“…Malacological research in Cambodia can be traced back to the 19 th century, but studies have been temporally and spatially sporadic. However, a small number of local investigations have been undertaken in the past decade (Vermeulen et al 2007(Vermeulen et al , 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…The species list of molluscan fauna from Cambodia was reviewed by Fischer (1973a-c). The endemic and monotypic slug, Cambodiparmarion doroshenkoi, was described from the south of Cambodia (Kuznetsov and Kuzminykh 1999) and Vermeulen et al (2007Vermeulen et al ( , 2019a reported land snails from south Cambodia and Vietnam, mainly focusing on Mekong Delta limestone in the southwest and the foothills of the southern Annamite range in the northeast. In addition, Hun et al (2019) discovered the giant land snail Bertia cambojiensis in Cambodia for the first time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation